Brief Communication: Effect of Post-Mating Pro Gestagen Administration on Pregnancy Rate in Crossbred Goats Following an Induced Estrus - Nava-Trujillo, Héctor; Chango-Villasmil, José; Finol-Parra, Geovanny; Maldonado-Suárez, Juan; Torres-Rodríguez, Paola; Carrillo-Fernández, Freygelinne; Gil-Huerta, Lidya (Revista Científica de la Facultad de Ciencias Veterinarias)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–>Estrus induced with progesterone or progestagens have low fertility compared to natural estrus. However, post-mating progesterone administration has been reported by increases embryo development and pregnancy rate; therefore the aim of this study was to evaluate the effect of post-mating progestagen administration on pregnancy rate after medroxyprogesterone acetate (MAP) induced estrus in crossbred goats. Estrus induction was started at 31.3 Ó 1.7 days post-partum with intra- vaginal sponges impregnated with 60 mg of MAP during 14 days and at time of sponge removal were applied 500 IU of eCG intramuscular. Estrus was detected every 6 hours from 24 hours onwards after sponge withdrawal. Goats were naturally mated with two entry bucks. Five days post-mating, mated goats were randomly assorted into two groups, control group (n=18), without any treatment, and MAP group (n=18), receiving a sponge with 60 mg of MAP for fourteen days. Ultrasonographyc diagnosis of pregnancy was performed at day 50 post-mating. MAP treatment, did not affect the pregnancy rate, with 44.4% (8/18) in MAP group, while in control group was 55.5% (10/18), P>0.05. In conclusion, MAP treatment with a sponge impregnated with 60 mg of MAP between days 5 and 19 post-mating did not affect the pregnancy rate after progestagen induced estrus during the early post-partum period in crossbred tropical goats